Determination of Nitrite Levels in Boiled White and Purple Cabbage Based on Boiling Time Variations - Eka Fitri Yanti; Nur Nadia Faridha; Bannan Muthi'tul Af'idah; Istiqomah; Mohammad Rofik Usman (ALKIMIA, 2026)
Cabbage is a type of vegetable that contains various vitamins such as vitamins A, C, and K. One of the chemical components found in cabbage is nitrite (NO₂). Nitrite is a nutrient formed naturally with concentrations depending on species variation, season, light, and fertilizer use. This study aims to determine the nitrite levels in boiled purple and white cabbage with varying boiling times using the UV-Vis spectrophotometric method. Additionally, this research evaluates whether the nitrite content in the boiled cabbage remains within the Acceptable Daily Intake (ADI). The extraction was carried out using distilled water with boiling time variations of 0, 5, 10, 15, and 20 minutes. Nitrite levels were determined using the UV-Vis spectrophotometric method. The nitrite content found in white cabbage for boiling durations of 0, 5, 10, 15, and 20 minutes were 1.672 ppm, 0.986 ppm, 1.037 ppm, 0.951 ppm, and 0.999 ppm, respectively. For purple cabbage, the levels were 1.627 ppm, <0.5 ppm, 0.624 ppm, 0.775 ppm, and <0.5 ppm, respectively. The nitrite contents in both white and purple cabbage were found to be safe according to the ADI value of 4.2 mg/kg for a person weighing 60 kg.